Merancang Usaha Tani Sayuran Skala Rumahan di Kelompok Ibu-Ibu PKK RT 03 RW 06 Kelurahan Mulyorejo - Esti, Erna Atiwi Jaya; Afdah, Umi; Rahayu, Yekti Sri (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
This article is based on the Community Service Program which seeks to help increase the insight and knowledge of residents to differentiate between subsistence and commercial scale vegetable production. This service program aims to increase the insight and skills of the residents of RT 03 RW 06 Mulyorejo Village, especially the Dasawisma group of PKK women in managing existing resources to implement home-scale vegetable farming. The approach method used is training and mentoring in vegetable business management for residents in RT 03. Community service activities are carried out in 3 stages, namely: (1) Socialization of activities; (2) Vegetable farming management training and bookkeeping; (3) Assistance for pioneering vegetable marketing. The results of the implementation of community service show that PKK women are able to allocate their resources to produce leaf vegetables and fruit vegetables on a home scale. The formation of production groups based on vegetable types greatly helps the availability of various types of vegetables to meet consumer demand around in the RT 03 RW 06. PKK women also have the ability to make simple bookkeeping although intensive assistance is needed to perfect the recording of expenditure transactions and income earned. The initial profits of vegetable farming run by PKK women during a growing season are still included in the business records of the Dasawisma group. A pilot agreement with an online vegetable shop has been agreed to expand the marketing network of PKK women in RT 03.